Study on the effect of emulsifiers on the pore structures of geopolymer prepared by emulsion templating - Zhuangzhuang Wang; Duyou Lu (Materials Research Express, 2020)
The metakaolin-based porous geopolymer were prepared by emulsion templating method with sunflower oil as the template agent. The effects of the type of emulsifiers with different ionic properties, including sodium stearate (SS), polyacrylamide (PAM), and cetyltrimethylammonium bromide (CTAB), which are respectively belonging to anionic, nonionic and cationic emulsifiers, on the paste viscosity, mechanical strength and pore structure of geopolymer were studied. Fourier transform infrared spectroscopy (FTIR) was used to characterize the influence of emulsion template on the geopolymerization. Scanning electron microscope (SEM) and Image-Pro Plus (IPP) software were used to examine the pore structure of geopolymers, including pore size distribution, average size and roundness of pores. Results indicate that geopolymerization is not significantly affected by the incorporation of emulsion template, while the average size, shape and connectivity of pores in geopolymer were significantly influenced by the type of emulsifiers. With the addition of SS, PAM, and CTAB, the average pore size were 18.1, 27.4, and 11.7 μ m, respectively, while the control is 18.9 μ m. Both the shape regularity and open porosity of pores were increased with SS and PAM, while no significant changes with CTAB. It is promising to make geopolymer with controllable macro pore structure by adjusting the types of emulsifiers in emulsion templating method by adjusting the oil-water interfacial tension and the particle dispersion.